2021
DOI: 10.1186/s40345-020-00206-0
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation of emotional regulation difficulties and mindfulness-based strategies in manic and remitted bipolar I disorder and major depressive disorder

Abstract: Background Both bipolar disorder and major depressive disorder are characterized by difficulties in emotion regulation. Little is known about which specific emotion regulatory patterns may be transdiagnostic versus disorder specific, and how such patterns change as a function of current mood states. Methods This preliminary investigation examined specific patterns of self-reported trait emotion regulation difficulties and mindfulness-based regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, the small sample size affected the results. Previous studies reported significant ED in patients with mood disorders compared to the general population, which was pervasive across diverse mood states including manic, depressive, and euthymic conditions ( 44 , 45 ). In particular, mood dysregulation is more severe in BD-II than in BD-I ( 46 , 47 ), which corroborates our study findings.…”
Section: Discussionmentioning
confidence: 95%
“…However, the small sample size affected the results. Previous studies reported significant ED in patients with mood disorders compared to the general population, which was pervasive across diverse mood states including manic, depressive, and euthymic conditions ( 44 , 45 ). In particular, mood dysregulation is more severe in BD-II than in BD-I ( 46 , 47 ), which corroborates our study findings.…”
Section: Discussionmentioning
confidence: 95%
“…In line with our results, only one preliminary study investigated differences in ED levels between patients in different mood states. It concluded that all patients with BD had alterations in ED, with no significant differences between groups 73 …”
Section: Discussionmentioning
confidence: 96%
“…The significance of this finding is highlighted when it is seen that affective temperaments - especially depressive - also have the highest correlation with this domain and can explain 53% of the variance of negative affectivity. Recent studies have confirmed the role of negative affect [ 45 ], anxiety [ 46 ], and emotion regulation problems [ 47 ] in patients with affective disorders. The results of a review also point to the relationship between affective temperaments - especially depressive temperament - and negative affect/neuroticism [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MDD showed higher scores than HCs only in the maladaptive facet of perceptual dysregulation. The incidence of psychotic symptoms, especially in patients with BD-II-I and emotional and perceptual dysregulation in depressed patients, has been previously reported [ 47 , 60 ]. Compared to other maladaptive domains, the psychoticism domain was more poorly predicted by affective temperaments.…”
Section: Discussionmentioning
confidence: 99%